Prosper's Chronicle: A Critical Edition and Translation of the Edition of 445 - Brook's, Deanna (Université d'Ottawa / University of Ottawa, 2014)
This thesis seeks to further research into Prosper’s chronicle and to counter Theodor Mommsen’s conclusions that Prosper made no editorial changes between the 445 and 455 editions of his chronicle. The ultimate result will be to prove that there were significant and deliberate alterations made by Prosper and to create a critical edition and translation of the chronicle of 445. The methodology includes establishing Prosper’s place in the Latin chronicle tradition, his alleged role as secretary to Pope Leo, his supposed residence in Rome and his theological views. Mommsen’s edition will then be used to compare the manuscripts of the 445 and 455 editions and to determine what differences exist. This comparison will show that Prosper not only continued his own chronicle but also edited it between 445 and 455. We will then fill the void left by Mommsen when he created only one edition by providing a critical edition and translation of the 445 chronicle for the first time.
Keywords: Prosper; Chronicles; Fifth-century theology; Western Roman Empire